Analisis Pengaruh Variasi Kuat Arus Pengelasan SMAW Terhadap Sifat Mekanik Material Baja JIS S45c (ASTM 1045) - Deka Dwi Adytama; Agus Suprayitno; Wawan Wawan (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2025)
The rapid advancement of technology today encourages every human being in matters related to the field of industrial or machinery needs, which has a function as a power transfer from the driving force (diesel engine or electric motor dynamo) to the engine to be driven, Gearbox is a component of a machineconsisting of a house for gears, In one of the uses of machine construction and in some components often involves professional welding techniques, one of which is welding using electric arc / Shielded Metal Arc Welding (SMAW), the selection of appropriate welding current parameters affects the strength and changes in the mechanical properties of a metal. The current used is too low will cause the difficulty of igniting the electric arc, and the electric arc that occurs is unstable, this test wants to examine using high carbon steel, namely JIS S45C STEEL (ASTM 1045) in the application for gears on the Gearbox through SMAW weldingusing electrodes (E11018-G) Ø3.2 mm with current variations of 90 A, 100 A and 110 A, and see its mechanical properties of NDT testing, tensile testing, and impact testing (charpy). The NDT test results obtained no indication of cracks in the variations of 90, A, 100 A and 110 A and the porosity indication only occurredin the variation of 100 A, in the Tensile test test obtained good results in the current variation of 90 A and the less good occurred in the variation of 100 A. In the Im test test, the results of the NDT test were obtained.